2005
DOI: 10.1007/s11910-005-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

Advances in clinical trials for amyotrophic lateral sclerosis

Abstract: Because treatments are not yet powerful enough to reverse the symptoms of amyotrophic lateral sclerosis (ALS), randomized placebo-controlled trials remain the gold standard for testing new therapies. To date, only one drug, riluzole, has been shown to slow the course of ALS, albeit in a very modest way. Since the approval of riluzole almost 10 years ago, there have been a number of negative trials, and we still await the discovery of a medication with a truly meaningful effect. With each study, our sophisticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Riluzole was able to effectively reduce ischemic neuronal damage in the spinal cord (Lang-Lazdunski et al, 1999), and prevent motoneuron death in vitro after exposure to glutamate agonists (Estevez et al, 1995). Moreover, clinical trials have proven that riluzole increased survival of a subset of amyotrophic lateral sclerosis (ALS) patients with bulbar onset, and it is one of the most promising drugs for the treatment of ALS (Bensimon et al, 1994;Gordon, 2005;Meininger et al, 1997). We have shown in our previous studies that systemic administration of riluzole in animals that had their lumbar ventral root avulsed and reimplanted prevented the death of motoneurons (Nó grá di and Vrbová , 2001), even if onset of treatment was delayed by 10 days (Nó grá di et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Riluzole was able to effectively reduce ischemic neuronal damage in the spinal cord (Lang-Lazdunski et al, 1999), and prevent motoneuron death in vitro after exposure to glutamate agonists (Estevez et al, 1995). Moreover, clinical trials have proven that riluzole increased survival of a subset of amyotrophic lateral sclerosis (ALS) patients with bulbar onset, and it is one of the most promising drugs for the treatment of ALS (Bensimon et al, 1994;Gordon, 2005;Meininger et al, 1997). We have shown in our previous studies that systemic administration of riluzole in animals that had their lumbar ventral root avulsed and reimplanted prevented the death of motoneurons (Nó grá di and Vrbová , 2001), even if onset of treatment was delayed by 10 days (Nó grá di et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential of NIV to attenuate the decline in FVC over time and that most ALS patients have some evidence of respiratory muscle weakness as early as the time of initial diagnosis (19,20), clinical trials of NIV are being designed to target the ALS population with an FVCw50% (11,12). A randomized, placebo-controlled trial of early NIV would be the ideal method for testing this new therapy (21). To our knowledge, sub-therapeutic (sham) NIV has never been used as a placebo control in a clinical study with ALS or any other neuromuscular disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life is a fundamental outcome measure in ALS research studies, but it is highly vulnerable to a placebo effect (27). The need for placebo controls is clearly recognized in ALS pharmaceutical trials (21,28), but this issue has not been considered previously for NIV trials in ALS (10). Clinical trials of NIV should be subject to the same rigorous methodological standards as drugs trials.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ALS patients face nearly the same prognosis today as they did 75 years ago when Lou Gehrig first brought the disease to public attention. Over the last decade, a number of promising preclinical compounds have advanced to clinical trials, but only riluzole has demonstrated even a modest effect on clinical outcomes (Gordon, 2005;Perrin, 2014).…”
Section: Preclinical Evaluation In the Absence Of Existing Therapiesmentioning
confidence: 99%
“…As noted above, a number of factors could be attributed to these failures: poorly designed preclinical or clinical studies (Doody et al, 2014;Gordon, 2005;Perrin, 2014), animal models that do not fully recapitulate the human condition (Blesa et al, 2012), or even a continued misunderstanding of a particular factor in the disease process (Cedernaes et al, 2014).…”
Section: Preclinical Evaluation In the Absence Of Existing Therapiesmentioning
confidence: 99%